Kelewatan Projek Landasan Keretapi Berkembar Elektrik Gemas-Johor Bahru dalam Era Pandemik - Sis, Nurul Fatehah; Masrom, Md Asrul Nasid; Khalid, Zailawati; Shafii, Haryati; Shareh Musa, Sharifah Meryam (Research in Management of Technology and Business, 2021)
In general, delay can be defined as an act of delay, postponement or postponement of the execution of work. Delays can also occur directly and indirectly will affect project completion and increase overall construction operating costs. In this study, the pandemic that hit around the world was one of the factors beyond expectations and beyond the jurisdiction of the contractor in addressing the cause of this delay. Therefore, this research aims to study the delays on the Gemas – Johor Bahru Railway Electrified Double-Tracking to identify the causes of delays in the track project and the steps taken by the contactor in overcoming the delays of the project. To achieve the objectives, this study uses qualitative methods as data collection through semi-structured interviews with construction site engineers, quantity surveyors and safety site supervisors at the railway track project site. This research found that all respondents agreed on the cause of delays faced by the project is with the implementation of the Movement Control Order (PKP) and also some other factors that cause delays. The measure used by the contractor to overcome this delay is to follow the instructions issued by the government, namely the SOP at the construction site. The results of this study are expected to be used as an effective measure that can be taken by any developer to continue infrastructure construction projects.